Investigating The Impact of Cause Related Marketing on Consumer Attitude and Purchase Intention - Galuh Mira Saktiana; Adhi Prakosa (Pelopor Publikasi Akademika, 2023)
Cause-related marketing (CRM) is a marketing program that closely relates to corporate social responsibility. The increasing popularity of CRM has led many researchers to investigate effective CRM campaign strategies. This study employs an experimental design with a factorial design to assess the impact of time duration, proximity, and congruence on brand attitudes and intentions. The study was conducted with college students from two cities in Indonesia, and statistical analyses, including t-tests and regression, were utilized. The results indicate that respondents' attitudes vary with respect to time duration and congruence, and attitudes towards brands related to CRM programs positively affect intentions. Therefore, marketers should consider the attributes of CRM, such as duration and congruence, to ensure that the program is accepted by consumers.